Shear Strengthening of Corbels with Carbon Fibre Reinforced Polymers (CFRP) - Ahmad, S.; Shah, A.; Nawaz, A.; Salimullah, K. (Materiales de Construcción, 2010)
Corbels constitute what are known as “disturbed” regions in concrete structures, where typical shear failure may be anticipated on the grounds of small shear span-to-depth ratios. The concentration of stress induced by the weight of girders on the very small loadbearing areas in corbels often causes cracking in bridges and other structures. Little experimental research can be found in the literature on the shear strengthening of corbels. In the present study, nine such members were tested. Two had no carbon fibre reinforced polymers attached, while CFRP laminates were externally bonded to the other seven, in a number of different spatial arrangements. Ultimate shear strength was found and compared for all specimens. The results showed that CFRP configuration and geometry directly affected corbel shear strength, which was higher in all the CFRPstrengthened corbels than in the controls. The highest strength values were recorded for specimens whose shear-critical area was wrapped in CFRP.